Health information needs of the visually impaired in urban centres: a cse study of Oyo State, Nigeria (2001)
This paper examines health information needs and its utilization by the visually impaired in urban centres in Oyo State. The main focus of the study was to determine the health problems for which the visually impaired seek health information in an attempt to live well. The sample population was made up of sixty visually impaired. They include twenty-eight (males) and thirty-two (32) females, and the instruments employed in collecting data include, questionnaire and interview. The analysis of the data revealed that the visually impaired needed different types of health information for their well-being in Oyo State. To achieve good patronage of the health information centres, there is need for the various contres to be better organised with the aim of improving thier services to the visually impaired